Production Optimization Through Horizontal Well Geometry : Toe-Up Vs Toe-Down - Dharma Arung Laby; Abdi Suprayitno; Amiruddin; Aprilno Alfa Kumasela; Abdul Gafar Karim; Darmiyati, Iin (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2021)
Horizontal wells are wells that are widely used in the oil and gas industry considering their effectiveness in increasing the productivity of a well. In field V, horizontal wells are not completely horizontal (90 degrees). Due to deviations in the geological formation, the drilled wells follow the formation dip. This study aims to determine the most optimal well model from several scenarios (toe-up, horizontal, or toe-down) and identify the dominant flow regime in the well. In this study, the author models well productivity and flow regimes with several scenarios. Such as the original scenario, true horizontal (90 degrees), toe-up (95 and 100 degrees) and toe-down (80 and 85 degrees). In each scenario, several different flow patterns or flow regimes can occur such as dispersed bubble flow, plug flow, annular flow, and slug flow. After comparing the productivity of each scenario, the results show that the toe-up scenario (100 degrees) has the highest oil production rate of 9401.8 STB/day, the original scenario 8599.7 STB/day, and the toe-down scenario (80 degrees) with 8237.6 STB/day has the lowest oil production rate. Therefore, toe-up (100 degrees) is the optimal well model used for horizontal wells in the V field compared to other scenarios. The gradient matching results for all well scenarios show a bubble flow pattern along the horizontal section of the well.